Copper-containing nanoparticles: Mechanism of antimicrobial effect and application in dentistry-a narrative review - Ma, Xinru; Zhou, Shiyu; Xu, Xiaoling; Du, Qin (Frontiers in Surgery, 2022)
Copper has been used as an antimicrobial agent long time ago. Nowadays, copper-containing nanoparticles (NPs) with antimicrobial properties have been widely used in all aspects of our daily life. Copper-containing NPs may also be incorporated or coated on the surface of dental materials to inhibit oral pathogenic microorganisms. This review aims to detail copper-containing NPs’ antimicrobial mechanism, cytotoxic effect and their application in dentistry.